PERAN PEMBELAJARAN LATANSA DALAM MEMBENTUK KARAKTER RELIGIUS PESERTA DIDIK DI KELAS 3 SDIT BUDI MULYO KULON PROGO - Anintyawati, Riska; Prayitna, Ananta Irman (Journal of Primary Education Research, 2024)
The research is motivated by the issues arising from the decline in children's character and the crucial role of schools in addressing this matter. As demonstrated by SDIT Budi Mulyo, which focuses on cultivating religious character and good morals, the implementation of Latansa learning has positively impacted students' character. This study aims to analyze the role of  Latansa learning in shaping the religious character of students at SDIT Budi Mulyo.This research is qualitative and employs a descriptive research method.  The results indicate that technological advancements have led to a decline in character education among children. To address this issue, it is essential to instill religious character from an early age, in line with the teachings of the Prophet Muhammad SAW. The solution identified is the effective implementation of Latansa learning in shaping students' religious character, enhancing religious adherence, and improving attitudes of respect towards parents and discipline regarding time.Throughout the study, the role of Latansa learning in shaping religious character was highlighted, emphasizing the importance of instilling religious values from an early age, particularly in elementary school. Latansa learning has proven effective in enhancing students' religious character. These findings align with previous research emphasizing the necessity of character education at all ages and the integration of religious education within the curriculum to develop noble morals and tolerance. Thus, Latansa learning can serve as an effective solution to counter the influence of technology and strengthen religious values among students.